2012
DOI: 10.1111/j.1754-9485.2012.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with subjective well‐being in cancer workers in Queensland

Abstract: Cancer workers' overall levels of SWB were similar to the national mean scores. Amount of time in direct patient care was linked with SWB, with an optimal time between 11 and 30 h per week associated with high SWB. The majority of the factors significantly associated with SWB were of a personal nature such as marital status and physical and mental health. These data provide a valuable baseline for future research in this area, especially in the area of interventions to promote SWB of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Only one of the 16 studies was longitudinal (Hakanen & Schaufeli, 2012), and this study found a positive association between engagement and life satisfaction and a negative association between engagement and exhaustion as well as depressive symptoms. Three studies found a link between engagement and general/psychological health (Freeney & Fellenz, 2013;Poulsen et al, 2012;Simbula, 2010), and one study showed mixed support for the positive relationship between engagement and various dimensions of work ability (Arilia et al, 2012). Three studies found mixed support for a negative association between engagement and dimensions of burnout, particularly emotional exhaustion (Hoigaard, Giske, & Sundsli, 2012;Simbula, 2010;Vera, Salanova, & Martin, 2010).…”
Section: Morale Outcomesmentioning
confidence: 99%
“…Only one of the 16 studies was longitudinal (Hakanen & Schaufeli, 2012), and this study found a positive association between engagement and life satisfaction and a negative association between engagement and exhaustion as well as depressive symptoms. Three studies found a link between engagement and general/psychological health (Freeney & Fellenz, 2013;Poulsen et al, 2012;Simbula, 2010), and one study showed mixed support for the positive relationship between engagement and various dimensions of work ability (Arilia et al, 2012). Three studies found mixed support for a negative association between engagement and dimensions of burnout, particularly emotional exhaustion (Hoigaard, Giske, & Sundsli, 2012;Simbula, 2010;Vera, Salanova, & Martin, 2010).…”
Section: Morale Outcomesmentioning
confidence: 99%
“…Physical activity after work has been shown to be an important factor in recovery (Rook and Zijlstra, 2006) as well as improving levels of subjective well being (Poulsen et al, 2012). Relaxation is another factor which contributes to the recovery process by diverting attention away from work and reversing the negative consequences of work-related stress (Hahn et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Hakanen and Schaufeli 202 found that engagement negatively predicted depressive symptoms from time 1 to time 2 (3-year interval) and from time 2 to time 3 (4-year interval) in a sample of dentists. Poulsen et al 205 found that engagement was positively associated with subjective well-being in a sample of cancer workers.…”
Section: General and Psychological Healthmentioning
confidence: 99%